TOURIST DECISION SUPPORT SYSTEM FOR HOT SPRINGS, THAILAND - Kewalin ANGKANANON; Renuka KHUNCHAMNAN; Benjamaporn KONGCHANA; Piyabud PLOADAKSORN (Geo Journal of Tourism and Geosites, 2024)
This research aimed to: 1) gather the needs of Thai and foreign tourists in using the Decision Support System for Hot Springs Tourism in Surat Thani; 2) Design and develop the Decision Support System using the concept of an agile method; and 3) Evaluate the effectiveness of the Decision Support System implementation. The agile method enabled the System to be developed to support both the Android and IOS in Thai and English. The users’ requirement was collected by using questionnaires with 30 Thai and 30 foreign tourists. The users’ evaluation data was collected by using questionnaires with 400 Thai and 400 foreign tourists. The results found that: 1) Thai and foreign tourists need information in seven aspects. Mo st tourists use iPhones and need similar information. 2) The design of the Decision Support System consists of searching travel routes, distance calculation, nearby attractions, and evaluation assessment function. 3) Foreign tourists had a slightly high er average score of overall opinions than Thai tourists which is at the highest level in all aspects. The Thai and foreign tourists found no significant difference with the overall opinions in using the Decision Support System (p> .05). In conclusion, the DSS for Hot Springs Tourism in Surat Thani was successfully developed for both Thai and foreign tourists. The findings indicate the system's effectiveness in supporting tourists and its potential to enhance tourism experiences in Surat Thani.